Strategi Pemulihan Ekosistem Di Taman Wisata Alam Tanjung Tampa Kabupaten Lombok Tengah - Alvin Sofiandi Nursyam; Taslim Sjah; Hayati Hayati (Universitas Mataram, 2023)
Tanjung Tampa Nature Tourism Park is part of the nature conservation areas. Nevertheless, this area has been facing problems of degrading forest function, driven by forest encroachment, illegal logging, and wildlife poaching. This study aims to formulate the strategies for ecosystem recovery at Tanjung Tampa Nature Tourism Park using qualitative descriptive research. The data were analyzed using SWOT (Strengths, Weaknesses, Opportunities, and Threats). The result shows the importance of ecosystem restoration at Tanjung Tampa Nature Tourism Park to be implemented by focusing on the strengths and opportunities. In addition, to develop forest management by advancing human resources' competence, strengthening synergies and collaboration among multi-stakeholders.